SMEGA - accounting and financial reporting guidelines for small and medium sized enterprises : level 3 guidance (UN New YorkUS, 2009)
Seeks to meet the needs of users and persons preparing financial statements for small and medium enterprises.
Keywords: ACCOUNTING